Physiological and genetic characterization of calcium phosphate precipitation by Pseudomonas species - Maxwell R. Fishman (Nature Portfolio, 2018)
Abstract Microbial biomineralization is a widespread phenomenon. The ability to induce calcium precipitation around bacterial cells has been reported in several Pseudomonas species but has not been thoroughly tested. We assayed 14 Pseudomonas strains representing five different species for the ability to precipitate calcium. Calcium phosphate precipitated adjacent to the colonies of all the Pseudomonas strains tested and also precipitated on the surface of colonies for several of the Pseudomonas strains assayed. The precipitate was commonly precipitated as amorphous calcium phosphate, however seven of the 14 Pseudomonas strains tested precipitated amorphous apatite in agar adjacent to the colonies. Out of the seven Pseudomonas strains that precipitated amorphous apatite, six are plant pathogenic. The formation of amorphous apatite was commonly observed in the area of the agar where amorphous calcium phosphate had previously formed. A transposon mutagenesis screen in Pseudomonas syringae pv. tomato DC3000 revealed genes involved in general metabolism, lipopolysaccharide and cell wall biogenesis, and in regulation of virulence play a role in calcium precipitation. These results shed light on the common ability of Pseudomonas species to perform calcium precipitation and the underlying genetic regulation involved in biomineralization.